Persepsi Masyarakat Terhadap Pelaksanaan Promosi Perpustakaan Umum Kota Padang di Kantor Arsip Perpustakaan dan Dokumentasi Kota Padang - Handayani, Vicha; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
The purposes of this study were: (1) to describe how the media shapes made by librarians in promoting Perpustakaan Umum Kota Padang, and (2) to dtermine how the public perception of the implementation of the campaign carried out Perpustakaan Umum Kota Padang. Data were collected through interviews and observations in the library of the office Arsip Perpustakaan dan Dokumentasi Kota Padang. The data were analyzed descriptively. Research findings are ineffective media promotion done by Perpustakaan Umum Kota Padang. So the conclusion is perseption of the society for less so positive and people are not aware of any promotions undertaken by Perpustakaan Umum Kota Padang. Keywords: promotion; perception